2020
DOI: 10.4143/crt.2019.210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Cancer History on the Clinical Outcomes in Advanced Breast Cancer: A Propensity Score–Adjusted, Population-Based Study

Abstract: PurposeDespite the rapid growing of cancer survivors, prior cancer history is a commonly adopted exclusion criterion. Whether prior cancer will impact the survival of patients with advanced breast cancer (ABC) remains uncertain.Materials and MethodsPatients with ABC diagnosed between 2004 and 2010 were identified using Surveillance, Epidemiology, and End Results (SEER) database. Timing, stage, and type were used to characterize prior cancer. Multivariable analyses using propensity score–adjusted Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(41 reference statements)
1
18
1
Order By: Relevance
“…However, subsequent subgroup analyses revealed that a prior cancer history could impair the survival of patients only when the interval time was less than two year. This time-frame finding was different from the study by Lin et al that demonstrated no survival detriment in patients with advanced breast cancer who had prior cancer outside the timeframe of 4 years [ 17 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…However, subsequent subgroup analyses revealed that a prior cancer history could impair the survival of patients only when the interval time was less than two year. This time-frame finding was different from the study by Lin et al that demonstrated no survival detriment in patients with advanced breast cancer who had prior cancer outside the timeframe of 4 years [ 17 ].…”
Section: Discussioncontrasting
confidence: 92%
“…We found that approximately 4.5 % of patients had exactly one non-prostate prior cancer before the diagnosis of APC. This proportion was similar to advanced breast cancer but lower than advanced lung cancer [ 6 , 17 ]. Besides, similar to studies reported by Bluethmann et al [ 16 ] and Murphy et al [ 18 ], our study suggested that the elderly patients were more likely to have a history of prior cancer than the younger patients.…”
Section: Discussionmentioning
confidence: 95%
“…The high prevalence of a cancer history among individuals with a new cancer diagnosis may have important implications for the delivery of cancer treatment and survivorship care. Some reports, including those conducted using SEER data, have documented inferior overall survival among patients with certain cancer types, including breast, prostate, colorectal, uterine, thyroid, melanoma, and bladder, who have a prior cancer diagnosis compared to those without, even after accounting for demographic and tumor characteristics 2‐5 . For patients with these cancer types, prior cancer history may therefore influence decisions surrounding treatment for the newly diagnosed cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the prevalence of the second or later cancer diagnoses may be consequential for several reasons. Some studies have suggested that, for certain cancer types, overall survival may be significantly lower for patients whose diagnosis is a second‐ or higher‐order primary, relative to those with a first primary cancer diagnosis 2‐5 . As a result, patients with a second or later primary cancer are often excluded from cancer clinical trials on the basis of their cancer history 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A SPM is defined as a cancer which arises independently in a new organ or tissue at least 2 months after the diagnosis of the prior primary cancer. Over 10% of younger adult cancer patients and around 25% of older adult cancer patients have been diagnosed with a SPM [9,10]. It has been reported to be associated with genetic susceptibility [11,12], the carcinogenic AGING adverse effects of cancer treatment [13], and behavioral risk factors such as smoking and alcohol intake [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%